PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATERI SISTEM EKSKRESI MANUSIA BERBASIS PROBLEM BASED LEARNING (PBL) KELAS X SMA - Laia, Haogoli (Universitas Nias Raya, 2025)
This research aims to develop LKPD based on Problem Based Learning. This type of research (Research and Development) uses the 4D development model. This research was tested on 15 class X Science students at SMA Negeri 2 Susua. To standardize products, three test stages are carried out, namely validity, practicality test and effectiveness test. The instruments used are assessment questionnaires using a Likert scale and evaluation test questions to determine student learning outcomes. The research results show that the LKPD based on the Problem Based Learning is very valid with a percentage of 90.4% and is suitable for use. The average value of practicality assessed by teachers is 3.5 and students are 3.5 in the very practical category. Student motivation results were in the very high category at 88.17% with an average cognitive score of 90.4 compared to previously using LKPD with an average score of 58.4% in the sufficient category. Based on the research results, the development of student worksheets (LKPD) based on Problem Based Learning (PBL) on human excretion material for class X SMA Negeri 2 Susua was declared valid, practical and effective for improving student learning outcomes. For future researchers, it is suggested that this problem based learning LKPD can be used as a reference in relevant research.